Linguodidactic Features of Authentic Materials in Agricultural English for Specific Purposes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides a theoretical and analytical investigation into the linguodidactic features of authentic materials in the context of English for Specific Purposes (ESP) within agricultural education. Authentic resources, such as scientific articles, monographs, technical documents, and interviews, are examined for their potential to enrich professional vocabulary, develop communicative competence, and bridge the gap between classroom-based language learning and real-world professional discourse. The study draws upon key theoretical frameworks, including Krashen’s Input Hypothesis, Ellis’s Task-Based Learning, and Cummins’s distinction between Basic Interpersonal Communication Skills (BICS) and Cognitive Academic Language Proficiency (CALP). It compares international practices from Germany, the Netherlands, and the United States with the realities of agricultural higher education in Uzbekistan, where reliance on artificially constructed teaching texts still prevails. Findings suggest that authentic materials are not supplementary but rather central pedagogical resources in ESP for agriculture. Recommendations are made for curriculum integration, use of global resources from FAO and the World Bank, and the adoption of multimedia authentic resources. The paper emphasizes the importance of aligning agrarian ESP instruction with global academic and professional standards.